2011
DOI: 10.1186/2045-709x-19-17
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of a primary spine care practitioner and its benefits to health care reform in the United States

Abstract: It is widely recognized that the dramatic increase in health care costs in the United States has not led to a corresponding improvement in the health care experience of patients or the clinical outcomes of medical care. In no area of medicine is this more true than in the area of spine related disorders (SRDs). Costs of medical care for SRDs have skyrocketed in recent years. Despite this, there is no evidence of improvement in the quality of this care. In fact, disability related to SRDs is on the rise. We arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 105 publications
0
51
0
Order By: Relevance
“…The collective experience of our graduates in managing difficult chronic patients is an advancement in chiropractic education and practice that should not be underestimated. As increasing numbers of MChiroMed graduates enter practice, they will have the knowledge, skills, expertise, and experience to be the true “spine care specialists” and to engage confidently and successfully in the difficult area of managing chronic spinal pain, which is the most common, costly, and disabling problem in society today 6, 7…”
Section: Advantages and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The collective experience of our graduates in managing difficult chronic patients is an advancement in chiropractic education and practice that should not be underestimated. As increasing numbers of MChiroMed graduates enter practice, they will have the knowledge, skills, expertise, and experience to be the true “spine care specialists” and to engage confidently and successfully in the difficult area of managing chronic spinal pain, which is the most common, costly, and disabling problem in society today 6, 7…”
Section: Advantages and Challengesmentioning
confidence: 99%
“…In North America, a growing movement advocates that chiropractors become the “primary spine care specialists.”6, 7 Since 2008, the chiropractic medicine program at the University of Zürich has positioned itself to be the model curriculum for chiropractors to become the primary spine (and extremity) care specialists. The purpose of this article was to discuss the Master in Chiropractic Medicine (MChiroMed) program at the University of Zürich and its advantages, opportunities, and challenges.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been suggested that some chiropractors could assume this broader role of primary care clinicians for the spine. 29,30 Before any health care profession or specialty can assume the role of primary care clinician for the spine, it is necessary that the clinician has the time, interest, education, and knowledge to assist patients in the shared decision making that is inherent in the IC process. With this objective in mind, a set of questions was developed to help patients gather information that might assist them in determining if a particular intervention that they are contemplating is in fact appropriate for them.…”
Section: Discussionmentioning
confidence: 99%
“…Although chiropractic has historically been centered on delivering spinal manipulation therapy (SMT), some have suggested that chiropractors may in fact act as primary care clinicians for spinal disorders and could thus be an important source of information for patients with LBP. 29,30 The primary objective of this study was to propose questions that may be helpful to educate patients considering treatment approaches to manage their LBP so that they may participate in shared and fully informed decision making. Secondary objectives were to analyze the information presented in IC documents currently used in outpatient clinics at ACC institutions to determine if these documents address the proposed questions and suggest improvements to IC documents for chiropractic management of LBP.…”
mentioning
confidence: 99%
“…The Council on Chiropractic education requires accredited colleges to train doctors of chiropractic to “practice primary health care as portal-of-entry provider for patients of all ages and genders.” 22 Although doctors of chiropractic cannot always function as primary care or portal-of-entry providers in all jurisdictions because of the realities of acceptance and reimbursement by entities such as payers, employers, and schools, 21 the training and ability to serve as portal-of-entry providers are central to the LACC chiropractic professional identity because early detection and referral for health conditions that are not optimally managed by the various therapeutic approaches offered by chiropractic doctors are critical for optimal relationship-centered care and outcomes. In the role of a spine care specialist, a doctor of chiropractic may expect to encounter serious pathology as a cause of spinal pain in 1% of patients, which for a busy practitioner could equate with several cases per year, 23 making effective diagnostic skills indispensable.…”
Section: Discussionmentioning
confidence: 99%